2021
DOI: 10.1186/s12870-020-02767-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of COMT gene family during the development of blueberry fruit

Abstract: Background Caffeic acid O-methyltransferases (COMTs) play an important role in the diversification of natural products, especially in the phenylalanine metabolic pathway of plant. The content of COMT genes in blueberry and relationship between their expression patterns and the lignin content during fruit development have not clearly investigated by now. Results Ninety-two VcCOMTs were identified in Vaccinium corymbosum. According to phylogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 70 publications
3
13
0
Order By: Relevance
“…The Methyltransf-2 domain was found in all 55 GmCOMTs gene sequences, with the majority of the genes having just one Methyltransf-2 domain; however, two genes (GmCOMT9 and GmCOMT19) had two Methyltransf-2 domains. In previous reports, the PtrCOMTs gene sequence of Populus trichocarpa contains only one Methyltransf-2 domain [48]; some blueberry VcCOMTs genes contain two or three Methyltransf-2 domains [20]. The 55 GmCOMT protein sequences all contain Methyltransf-2 domain, so they are relatively conservative; meanwhile, in the analysis of motifs, most of the motifs are relatively conservative in the two groups.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The Methyltransf-2 domain was found in all 55 GmCOMTs gene sequences, with the majority of the genes having just one Methyltransf-2 domain; however, two genes (GmCOMT9 and GmCOMT19) had two Methyltransf-2 domains. In previous reports, the PtrCOMTs gene sequence of Populus trichocarpa contains only one Methyltransf-2 domain [48]; some blueberry VcCOMTs genes contain two or three Methyltransf-2 domains [20]. The 55 GmCOMT protein sequences all contain Methyltransf-2 domain, so they are relatively conservative; meanwhile, in the analysis of motifs, most of the motifs are relatively conservative in the two groups.…”
Section: Discussionmentioning
confidence: 95%
“…Analysis of gene structure and conserved domains showed that all COMTs have a cterminal catalytic domain named Methyltrans-2, including a SAM/SAH binding pocket and a substrate binding site. Some of them show a common structure, the N-terminal domain, called dimerization [20]. The dimerization domain of LBD has been proposed, forming a helical structure, presenting a hydrophobic surface, which is formed by nine repeating heptapeptide motifs, containing hydrophobic residues at positions one and eight, and hydrophobic or charged amino acids with hydrophobic side chains at position five.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the phylogenetic tree was constructed from the alignment results using neighbor-joining (NJ) method. The phylogenetic tree was annotated and beautified by using iTOL online software ( , accessed on 24 July 2021) [ 39 , 40 ]. Additionally, we downloaded the genomic information of A. thaliana (TAIR10.1; , accessed on 8 July 2021) and a related species called Acer yangbiense (AYv1.1; , accessed on 29 July 2021) from the NCBI website and analyzed the collinearity with the information for the three species using TBtools [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genes related to sugar and organic acids are up-regulated during fruit development [17]. Genome-wide analysis showed that high expression levels of Vaccinium corymbosum caffeic acid O-methyltransferase (VcCOMT) family genes during the development of blueberry fruit may contribute to greater fruit firmness [18]. The process of transition from flower to fruit involves the anthocyanin pathway, transcription factor-related genes, sugar-related genes, hormone-related genes, and photosynthesis.…”
Section: Introductionmentioning
confidence: 99%